Human T-Lymphotropic Virus-1/2 Infection in Central Brazil Prisons: A Multicenter Study - Melo Bandeira, Larissa; Moreira Puga, Marco Antonio; Croda, Julio; Pompílio, Maurício Antonio; Amianti, Carolina; Rocha de Rezende, Grazielli; Coimbra Motta-Castro, Ana Rita (Frontiers in Microbiology, 2022)
Human T-lymphotropic virus (HTLV) infection is endemic in some group populations. Prisoners are at high risk of acquiring HTLV infection mainly due to the environment of closed penal institutions, socioeconomic conditions, and risk behaviors. This study aimed to investigate the prevalence, the occurrence of new cases of HTLV infection after a 1-year follow-up, and circulating subtypes of HTLV-1 among prisoners from twelve closed prisons in Mato Grosso do Sul state, Central Brazil. A total of 1,507 prisoners were randomly enrolled in the cross-sectional study. Out of the 1,507 participants, 1,000 prisoners, susceptible to HTLV infection, were included in the prospective cohort study. In the cross-sectional study, serological evidence of HTLV infection was 0.4% (CI 95%: 0.1-0.7), tested for anti-HTLV antibodies by enzyme-linked immunosorbent assay (ELISA). Three samples were positive for HTLV-1, two samples were positive for HTLV-2, and 1 sample was indeterminate by the Western blot method. The presence of HTLV proviral DNA was detected in all positive samples by amplification of the HTLV tax gene through nested-PCR. Phylogenetic analysis showed that HTLV-1 samples belonged to the Cosmopolitan subtype Transcontinental subgroup. From a cohort of 1,000 individuals, no new case of HTLV infection was detected. Although the prevalence rate of HTLV infection found in this study was similar to that observed in the Brazilian general population, the lack of access to preventive interventions and harm reduction measures all contribute to increasing the risk of HTLV transmission and acquisition among this key and vulnerable population.